CONCEPTUAL FOUNDATIONS OF NATIONAL SPIRITUALITY AND MORAL EDUCATION IN THE WORKS OF ABDULLA AVLONI (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the conceptual foundations of national spirituality and moral education in the works of Abdulla Avloni, one of the leading Jadid educators of early 20th-century Turkestan. Drawing on his pedagogical texts such as Turkiy Guliston yoxud Axloq (“Turkic Gulistan or Morality”), Birinchi Muallim (“First Teacher”) and Ikkinchi Muallim (“Second Teacher”), the study analyzes how Avloni integrates national values, religious–ethical principles, and modern knowledge into a unified educational ideal. His views are considered in the broader Jadid movement, which sought to harmonize national and universal values, promote enlightenment, and form a morally upright, patriotic generation. The article argues that Avloni’s synthesis of morality, spirituality, and national consciousness represents a systematic concept of character education grounded in national culture yet open to global civilization. It also highlights the contemporary relevance of these ideas for the moral and spiritual upbringing of youth in “New Uzbekistan,” where the Jadid heritage is seen as a key resource for strengthening national identity and preventing moral and ideological crisis.
Keywords: Abdulla Avloni, national spirituality, moral education, Jadid pedagogy, national values, youth upbringing, enlightenment, patriotism.